Holodomor, Famine in Ukraine, 1932-1933: A Crime against Humanity or Genocide? - Renate Stark (Irish Journal of Applied Social Studies, 2010)
Famines in the main are man-made and not merely caused by the occurrences of food shortages, due to natural disasters. This article discusses the theories of famine in relation to food entitlement and adverse government policy. In the first part the focus is on the introduction of theories of famine, where it is examined in what way the entitlement and distribution of food, rather than food shortage, is often the underlying cause for famines. Famines are strongly enmeshed in either direct or indirect political decisions. Consequently, political systems have often intentionally created famine conditions and used starvation as a mechanism of repression. This fact makes these government officials some of history’s worst criminals. In the second part, this article examines the case of Holodomor in Ukraine in 1932-33 and illustrates that not only political economy and forced collectivisation, but the intentional faminogenic behaviour of Stalin and a small group of his government officials, caused devastating starvation and the deaths of millions of people. This case moves the study of famine into the field of international law, in which Ukraine’s quest for UN recognition of Holodomor not only as a crime against humanity, but also as genocide, could be regarded as justified.